The effect of beverages containing caffeine on the tear film parameters: an observational study - Almutleb, Essam Saad; El-Hiti, Gamal Abdel-Rahman; Alotibi, Fahad Modhy; Al-Grian, Muqrin Mohamad; Almutairi, Meznah Saud; Masmali, Ali Mohammed (Journal of the Pakistan Medical Association, 2025)
Objective: To assess the short-term effect of consuming two beverages containing caffeine on tear film parameters. Method: The observational study was conducted at the King Saud University, Riyadh, Saudi Arabia, from March 5 to April 28, 2016, and comprised males aged 18-34 years. The subjects were randomised into three equal groups. Group A consumed Pepsi (355mL), group B consumed Mountain Dew (355mL), and group C consumed nothing. The phenol red thread, tear ferning, and tear breakup time tests were performed in both eyes of each subject at the baseline and an hour after consumption. Data was analysed using SPSS 22. Results: Of the 105 male subjects with mean age 23.6±3.5 years, 35(33.3%) were in group A with mean age 23.8±3.8 years, 35(33.3%) were in group B with mean age 23.8±3.7 years, and 35(33.3%) were in group C with mean age 23.4±3.4 years. Significant differences were noted in the phenol red thread and tear breakup time scores in groups A and B compared to the baseline (p<0.05), while the difference was not No significant (p>0.05) for tear ferning grades. Group C showed no significant difference (p>0.05) on any count. Conclusion: The consumption of two caffeinated drinks significantly altered tear film stability and volume. Tear breakup time was increased, while tear volume decreased, but there was no significant effect on tear quality. Key Words: Males, Dry eye syndromes, Eye abnormalities, Risk factors, Anticholinergic agents.